2014
DOI: 10.1155/2014/958621
|View full text |Cite
|
Sign up to set email alerts
|

Moringa oleiferaSupplemented Diets Prevented Nickel-Induced Nephrotoxicity in Wistar Rats

Abstract: Background. The Moringa oleifera plant has been implicated for several therapeutic potentials. Objective. To evaluate whether addition of M. oleifera to diet has protective effect against nickel-induced nephrotoxicity in rats. Methodology. Male Wistar rats were assigned into six groups of five. The rats were given oral exposure to 20 mg/kg nickel sulphate (NiSO4) in normal saline and sustained on either normal diet or diets supplemented with Moringa oleifera at different concentrations for 21 days. 24 hours af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
22
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 18 publications
7
22
1
2
Order By: Relevance
“…These findings were confirmed by histological examinations, which revealed an amelioration of the hepatic and kidney damages induced by drugs, in animals treated with Moringa oleifera leaves. Similar results were obtained by Adeyemi and Elebiyo [ 162 ] in rats co-treated with Moringa oleifera leaves and NiSO 4 in order to induce nephrotoxicity. Finally, Das et al [ 123 ] observed a reduction of ALT, AST and ALP and a lower liver damage in rats fed with high fat diet and co-treated with Moringa oleifera leaves, suggesting a potential role of the leaves in the prevention of nonalcoholic fatty liver disease (NAFLD).…”
Section: Pharmacologysupporting
confidence: 88%
“…These findings were confirmed by histological examinations, which revealed an amelioration of the hepatic and kidney damages induced by drugs, in animals treated with Moringa oleifera leaves. Similar results were obtained by Adeyemi and Elebiyo [ 162 ] in rats co-treated with Moringa oleifera leaves and NiSO 4 in order to induce nephrotoxicity. Finally, Das et al [ 123 ] observed a reduction of ALT, AST and ALP and a lower liver damage in rats fed with high fat diet and co-treated with Moringa oleifera leaves, suggesting a potential role of the leaves in the prevention of nonalcoholic fatty liver disease (NAFLD).…”
Section: Pharmacologysupporting
confidence: 88%
“…Our results were in accordance with those reported by Amudha and Pari [2], who mentioned a significant increase in the relative kidney weight in Nitreated male rats. However, our results were opposing those reported by Dahmen-Ben Moussa et al [21] and Adeyemi and Elebiy [20] who exhibited that Ni treatment resulted in a significant decrease in relative kidney weight. In the present work, coadministration of methionine prevented changes in relative kidney weight and body weights.…”
Section: Bouhalit and Kechridcontrasting
confidence: 99%
“…animal growth and increase in organ-somatic index [19,20]. Our results were in accordance with those reported by Amudha and Pari [2], who mentioned a significant increase in the relative kidney weight in Nitreated male rats.…”
Section: Bouhalit and Kechridsupporting
confidence: 93%
See 1 more Smart Citation
“…The leaf extracts have shown to decrease the acetylcholine esterase activity, thereby improving cholinergic function and memory. 36 Adeyemi et al, 37 showed that moringa in diet can increase protein content and decrease levels of urea and creatinine in blood, preventing renal dysfunction. Moringa decreased acidity in gastric ulcers by a percentage of 86.15 and 85.13 at doses of 500mg and 350mg, respectively and therefore can be used as an antiulcer agent.…”
Section: Other Diseasesmentioning
confidence: 99%